Pengaruh Penambahan Tepung Kacang Merah Terhadap Daya Terima Basreng Ikan Cakalang - Oki, Alexandro; Niron, Maria F. Vinsensia D.P Kewa; Sine, Juni Gressilda Louisa (Kupang Journal of Food and Nutrition Research, 2025)
Protein-energy malnutrition (PEM) is a nutritional disorder that arises from low energy and protein consumption in the daily diet, and is influenced by certain health conditions. According to the 2023 Indonesian Health Survey (SKI) data, 29.7% of children in East Nusa Tenggara Province are malnourished. This study aims to evaluate the impact of adding red bean flour on the acceptability level and macro-nutrient content of cakalang fish basreng products. The study used a Completely Randomized Design (CRD) with red bean flour additions of 10%, 20%, and 30% in sequence, involving 30 panelists. The organoleptic test results showed that the average liking level (color, aroma, texture, and taste) fell into the “somewhat liked” to “liked” category. The normality test results for color, aroma, texture, and taste indicated that all the data presented were not normally distributed. Statistical test results using the Kruskal-Wallis test showed that there was no significant effect on color, aroma, texture, and taste in each treatment. Nutritional value calculations showed that the addition of red bean flour significantly contributed to an increase in the macro-nutrient content of skipjack tuna basreng. It is hoped that future researchers will use a drying oven in the red bean drying process to minimize cross-contamination from the surrounding environment.